Uma análise das ações de assistência estudantil no contexto do Instituto Federal de Educação, Ciência e Tecnologia de Sergipe - Nascimento, Ana Paula Leite (2014)
This research conducted a study about the Student Assistance, having as object the analysis of the implementation of their actions in the context of professional, scientific and technical education at the Federal Institute of Education, Science and Technology of Sergipe (IFS). In the course of this study we characterize the expressions of expansion inherent in the recent educational reform in the context of the IFS process, we conducted a survey of the Student Assistance actions developed in the setting of IFS, and analyzed the budgetary aspects of the IFS Student Assistance before the expansion process the Federal Network of Professional Education, Science and Technology. The study was exploratory, being focused predominantly qualitative nature of the research associated with some quantitative dimensions of the object. The universe consisted of three campuses of the IFS: Aracaju, Lizard and St. Kitts, in the period 2008-2012. The methodological procedures resorted to bibliographic and documentary research. During data collection, we used a script indicators to support the analysis of documents based on the objectives and hypotheses of the study, whose analysis was guided by the dialectical method. How principiais results highlight the quantitative expansion of access to educational courses of different modalities offered at IFS denotes incompatibility with access to actions of stay, confirming the hypothesis that the expansion of the Federal Network of Vocational Education, Scientific and Technological reflects insufficient democratization Share of Student Assistance in meeting the everyday demands of students of IFS. We have also noticed that despite the growth of budget allocation identified grow at the same time, demands for these actions, context confirms the hypothesis that the Student Assistance under the IFS, undergoes